Cause-specific mortality in adult epilepsy patients from Tyrol, Austria: hospital-based study - Claudia A. Granbichler; Willi Oberaigner; Giorgi Kuchukhidze; Gerhard Bauer; Jean‐Pierre Ndayisaba; Klaus Seppi; Eugen Trinka (2014)
Epilepsy is a devastating condition with a considerable increase in mortality compared to the general population. Few studies have focused on cause-specific mortality which we analyse in detail in over 4,000 well-characterized epilepsy patients. The cohort comprised of epilepsy patients ≥ 18, treated between 1970 and 2009 at the epilepsy clinic of Innsbruck Medical University, Austria, and living in the province of Tyrol, Austria. Epilepsy diagnosis was based on ILAE guidelines (1989); patients with brain tumor were excluded. Deceased patients and causes of death (ICD-codes) were obtained via record linkage to the national death registry. We computed age-, sex-, and period-adjusted standardized mortality rates (SMR) for 36 diagnoses subgroups in four major groups. Additional analyses were performed for an incidence cohort. Overall cohort: 4,295 patients, 60,649.1 person-years, 822 deaths, overall SMR 1.7 (95 % CI 1.6-1.9), highest elevated cause-specific SMR: congenital anomalies [7.1 (95 % CI 2.3-16.6)], suicide [4.2 (95 % CI 2.0-8.1)], alcohol dependence syndrome [3.9 (95 % CI 1.8-7.4)], malignant neoplasm of esophagus [3.1 (95 % CI 1.2-6.4)], pneumonia [2.7 (95 % CI 1.6-4.2)]. Incidence cohort: 1,299 patients, 14,215.4 person-years, 267 deaths, overall SMR 1.8 (95 % CI 1.6-2.1), highest elevated cause-specific SMR congenital anomalies [10.8 (95 % CI 1.3-39.3)], suicide [6.8 (95 % CI 1.4-19.8)], alcohol dependence syndrome (6.4 [95 % CI 1.8-16.5)], pneumonia [3.9 (95 % CI 1.8-7.4)], cerebrovascular disease at 3.5 (95 % CI 2.6-4.6). Mortality due to mental health problems, such as suicide or alcohol dependence syndrome, malignant neoplasms, and cerebrovascular diseases was highly increased in our study. In addition to aim for seizure freedom, we suggest improving general health promotion, including cessation of smoking, lowering of alcohol intake, and reduction of weight as well as early identification of psychiatric comorbidity in patients with epilepsy.